An Exploratory Factor Analysis of Classroom Management and Student Learning Motivation in Senior High Schools - Helmiyatun; Ahmad; Taqiudin , Muhamad (Global Action and Education for Society, 2025)
This study is motivated by the importance of understanding students’ perceptions of classroom management and learning motivation, as both aspects play a crucial role in achieving educational goals at the senior high school level. The purpose of this research is to develop and examine the construct validity of an instrument designed to measure students’ perceptions of classroom management and learning motivation. The method employed was Exploratory Factor Analysis (EFA), applied to data collected through questionnaires distributed to high school students. The analysis revealed seven emerging factors, six of which had significant item loadings. The Kaiser-Meyer-Olkin (KMO) value of 0.58 and a significant Bartlett's test result indicated that the data were suitable for further factor analysis. The identified factors represent various essential dimensions within the context of classroom management and student motivation. Based on these findings, it can be concluded that the developed instrument demonstrates adequate construct validity and can serve as a relevant measurement tool in the context of senior high school education.